Management of severe left main bronchomalacia in an infant with a balloon expandable bare metal coronary stent: a case report - Efua H. Bolouvi; Michael D. Seckeler; Angelina Price; Wayne Morgan; Brian Lightwine; Kenneth W. Liechty (Journal of Pediatric Surgery Case Reports)
Introduction: Managing bronchomalacia in infants represents a significant challenge. Surgical strategies such as aortopexy and tracheopexy have variable outcomes in distal airway disease. Stent placement is typically reserved as a last resort in selected cases. Case presentation: A 4-month-old ex-34-weeker infant status-post neonatal repair of a large omphalocele was re-intubated six weeks post-operatively for severe respiratory distress. Despite escalating positive-end expiratory pressure, bronchodilators, and airway clearance, the respiratory function continued to decline. Bronchoscopy showed severe left main bronchomalacia and bronchial stenosis, confirmed by chest computerized tomography (CT). There was near complete occlusion of the left main bronchus, but with patent distal airway. A 4.5 mm × 15 mm bare metal coronary stent (Resolute Onyx Frontier) was placed in the left main bronchus under fluoroscopic and bronchoscopic guidance. This led to an immediate improvement in lung mechanics, with subsequent extubation. The stent was electively removed after 11 weeks. However, re-occlusion occurred within 24 hours due to airway compression, which was managed with the placement of a second stent (5 mm × 15 mm). The symptoms resolved completely, and the patient was discharged home at the age of 10 months. He was subsequently managed at a different hospital. At the age of 14 months the stent was removed. Shortly after the removal, he had a recurrence of the left lung collapse and a respiratory infection requiring extracorporeal membrane oxygenation (ECMO). An 8 mm × 20 mm stent was then placed to recruit the left lung and allow ECMO decannulation. He remains with the stent in place. Conclusion: Bare metal coronary stents appear to be an effective temporizing management option for infants with severe bronchomalacia who fail standard non-operative measures, allowing time for the airway to become more rigid.